In Vivo Characteristics of Nondegenerated Adjacent Segment Intervertebral Foramina in Patients With Degenerative Disc Disease During Flexion-Extension. Issue 6 (15th March 2017) - Cha, Thomas D.; Moore, Gregory; Liow, Ming Han Lincoln; Zhong, Weiye; Wu, Minfei; Wang, Shaobai; Kang, James D.; Wood, Kirkham B.; Li, Guoan
Abstract : Study Design: In vivo patient biomechanical study. Objective: To investigate the dimensions of lumbar intervertebral foramen (LIVF) of patients with degenerative disc disease (DDD) during a flexion-extension motion of the body. Summary of Background Data: LIVF narrowing may result in nerve root compression. The area changes of degenerated and adjacent nondegenerated LIVFs in DDD patients under physiologic loading conditions are unknown. Methods: Nine symptomatic low back pain patients with radiological evidence of L4-S1 DDD were recruited. Each subject was magnetic resonance imaging scanned for construction of three-dimensional lumbar vertebral models, and fluoroscopically imaged when the body extended from 45 flexion to full extension for reconstruction of LIVF dimensions. The data of the adjacent segment L3/4 and diseased segments L4/5 and L5/S1 were compared with a normal control group at 45 flexion, upright, and full extension of the body. Results: The mean LIVF areas of DDD segments were significantly smaller than those of the normal subjects in all positions ( P  <0.05). In upright position, the LIVF areas of the DDD patients were 32.8% and 33.6% smaller than the normal subjects for L4/5 and L5/S1, respectively. For the adjacent L3/4, the LIVF area of the DDD patients was 32.3% smaller than that of the normal controls ( P  <0.05). The total change of L3/4 LIVF area in DDD patients from flexion to extension was significantly smaller than that of the normal subjects, but the changes in L4/5 and L5/S1 LIVF areas were similar between the two groups ( P  >0.05). Conclusion: Similar reductions of the LIVF dimensions were observed at the adjacent and the involved levels of the DDD patients, implying that biomechanical changes might have already occurred at the adjacent segment despite the lack of radiographic evidence of degeneration. Subsequent research should focus on the effects of surgical fusion on the biomechanical features of the adjacent segment. Level of Evidence: N/A